PENGARUH JENIS ISOLAT LIGNIN DAN NISBAH MOL L/F PADA PEREKAT LIGNIN FORMALDEHIDA TERHADAP KETEGUHAN REKAT KAYU LAPIS TUSAM * - Adi Santoso; Surdiding Ruhendi; Suminar S Achmadi; Endang Suhendang (Pusat Penelitian dan Pengembangan Hasil Hutan, 1995)
It has been known that lignin can be used as plywood adhesive for exterior purpose. The sources of lignin are black liquor indulin-AT (commercial lignin).A study on lignin formaldehyde resin making from black liquor and indulin-AT was done and the results were used to predict the effect of lignin isolate type and L/F mole ratio on plywood bonding strength. The results show taht the type of lignin isolate and L/F mole ratio have highly significant effect on plywood bonding strength. The mole ratio L/F of 1 : 1.50 and 1:1.75 by lignin isolate from indulin-AT result in plywood bonding strength about 7.5 kg/cm2 and 8.8 kg/cm2, respectively. The bonding strength of these plywood conforms with the 1983 Japanese standard for exterior purpose.